Controlling Windu shrimp quality using apriori algorithm through smartphone-based application - Firdaus K. Gani; Rahmad Hidayatullah S; Rahmat Faisal Wahyudi; Satria Nur Hidayatullah (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
Shrimps are Indonesian most valuable export commodity and one of them is Windu (Penaeus monodon). Windu is Indonesian native and is the most well-known species among the shrimp farmers in Indonesia especially in Aceh and East Java. This species is vulnerable to several viral diseases that can affect to the productivity decrease particularly for small farmers. Lack of knowledge about windu epidemic diseases and its handling ways in traditional farmers are keys of this species' productivity decrease. Using apriori algorithm trough application in smartphone which is the amount of users in Indonesia increases every year is expected to be an effective way to solve these problems. Apriori algorithm is better in finding associative rules pattern than any other methods, and is the most efficient in memory usage. In this research, this apriori algorithm is used for defining the disease indication using the data from infected windu's physical characteristics and behaviours.
Keywords: 650; apriori algorithm; smartphone-based application; windu shrimp